Casarett and Doull's toxicology the basic science of poisons - Klaassen, Curtis D.; Casarett, Louis J.; Doull, John 1922 (McGraw-Hill Education, 2013)
This book offers an overview of the biomedical and environmental aspects of toxicology. Combined with the thinking by the field's foremost scholars, ths title offers coverage of general principles, modes of action, and chemical-specific toxicity